MEDIASI DALAM PERKARA PERCERAIAN OLEH HAKIM PENGADILAN AGAMA - Ivanda, Alda Christa; Martika Dini Syaputri (Collegium Studiosum Journal, 2024)
Marriage includes 2 (two) individuals, namely a man and a woman who have the aim of forming a happy family. Every individual in building a family has rights and obligations that must be implemented and obtained. If one of these obligations is ignored, it can hinder the achievement of the goals of the marriage itself. Divorce is a process of ending a marital relationship. Before a divorce agreement is reached, mediation will be carried out between the two parties with the aim of reconciling the two parties so that there is no need for a divorce. The method used in conducting research is qualitative using a descriptive approach. This approach refers to a systematic and accurate depiction of facts and characteristics of research objects and subjects. Mediation in resolving civil disputes, especially in the context of divorce in the Religious Courts, has been carried out in accordance with applicable regulations. Factors inhibiting the success of mediation in resolving civil cases, especially divorce in the Religious Courts, include strong differences of opinion regarding divorce, prolonged conflict, lack of good intentions to reconcile, and the influence of mental or emotional factors.